Aesthetics of Humanitarian Online Course - A. S. Robotova (Высшее образование в России)
This material is the last text of Prof. A.S. Robotova received by the Editor. The text is theses to a possible article on her favorite humanitarian topic. The paper addresses the issues of the specific of online humanitarian text. The resources of online course may be found in the common for teacher and students time-space context, their emotional and cognitive affinity. The author believes that special attentions should be paid to composition and semantic expressiveness of the content. It may be reached by intellectual tension, clash of texts, facts and data, which switches on the mechanism of internal dialogue and activates student’s interest.